2015
DOI: 10.1038/ncomms9668
|View full text |Cite
|
Sign up to set email alerts
|

Atomic cobalt on nitrogen-doped graphene for hydrogen generation

Abstract: Reduction of water to hydrogen through electrocatalysis holds great promise for clean energy, but its large-scale application relies on the development of inexpensive and efficient catalysts to replace precious platinum catalysts. Here we report an electrocatalyst for hydrogen generation based on very small amounts of cobalt dispersed as individual atoms on nitrogen-doped graphene. This catalyst is robust and highly active in aqueous media with very low overpotentials (30 mV). A variety of analytical technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
920
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,431 publications
(966 citation statements)
references
References 47 publications
32
920
2
3
Order By: Relevance
“…To this end, experimental research has shown that oxide supports such as MgO, 20 FeO x , 19 SiO 2 22 and TiO 2 23 or graphitic layers 24 can anchor single metal atoms and hence allow synthesis of SACs by using the mass-selected soft-landing technique, improved wet chemistry methods, or atomic layer deposition methods. 19,20,24 Particularly, two-dimensional (2D) materials with a large surface area and high thermal stability, such as graphene, [25][26][27][28][29] graphyne, 30,31 MoS 2 32 and freestanding hexagonal boron nitride monolayers (h-BN), 33,34 can be used as prominent supports to host single metal atoms, which exhibit superb catalytic activity for CO oxidation. [35][36][37][38] Recent experimental studies also showed that Ag supported by BN nanosheets with good thermal stability can be used as an effective catalyst for the reduction of p-nitrophenol 39,40 and the methanol oxidation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, experimental research has shown that oxide supports such as MgO, 20 FeO x , 19 SiO 2 22 and TiO 2 23 or graphitic layers 24 can anchor single metal atoms and hence allow synthesis of SACs by using the mass-selected soft-landing technique, improved wet chemistry methods, or atomic layer deposition methods. 19,20,24 Particularly, two-dimensional (2D) materials with a large surface area and high thermal stability, such as graphene, [25][26][27][28][29] graphyne, 30,31 MoS 2 32 and freestanding hexagonal boron nitride monolayers (h-BN), 33,34 can be used as prominent supports to host single metal atoms, which exhibit superb catalytic activity for CO oxidation. [35][36][37][38] Recent experimental studies also showed that Ag supported by BN nanosheets with good thermal stability can be used as an effective catalyst for the reduction of p-nitrophenol 39,40 and the methanol oxidation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…10 Graphene, compared to its other carbon counterparts, is unique because of its exceptional electrical properties, huge surface area (42600 m 2 g -1 ) and 2D nature, and thus has been explored extensively for various fuel-cell applications. [12][13][14] However, for catalytic applications, it has been shown that graphene is highly active at its edges compared to its basal plane. 15,16 The increased density of states at the edge defects compared to basal plane makes the edges of graphene have faster capabilities of electron transfer to oxidize or reduce various chemical compounds in the solution phase.…”
Section: Introductionmentioning
confidence: 99%
“…Although attempts have been made to elucidate the roles of different metals in affecting the catalytic activity of M-N-Cs, they were severely complicated by the fact that the physicochemical characteristics (for example, degree of graphitization, carbon structure, nitrogen-doping type and surface area) of the synthesized M-N-Cs are highly dependent on the metal identity and any observed differences in catalytic activity are highly convoluted with various structural characteristics 30,31 . These limitations represent the key challenges in establishing the exact structure-to-property correlation in SACs, which is essential for the rational design and synthesis of new SACs with tailored activities for wide ranges of electrocatalytic processes [32][33][34] . Here, we report a general approach to a series of atomic 3d metals embedded in nitrogen-doped holey graphene frameworks (M-NHGFs, M = Fe, Co or Ni), unambiguously determining their atomistic structures and correlation with electrocatalytic activity towards the oxygen evolution reaction (OER); a reaction that is essential for diverse clean energy technologies including water splitting, CO 2 reduction and rechargeable metal-air batteries 2,[35][36][37] .…”
mentioning
confidence: 99%